Tea Consumption and Diabetes: A Comprehensive Pharmacological Review of Black, White, Green, Oolong, and Pu-erh Teas - Ochuko L. Erukainure; Chika I. Chukwuma; Jennifer Nambooze; Satyajit Tripathy; Veronica F. Salau; Kolawole Olofinsan; Akingbolabo D. Ogunlakin; Osaretin A. T. Ebuehi; Jeremiah O. Unuofin (Plants)
Diabetes is one of the major non-communicable diseases whose physiological complications are linked with a higher risk of mortality amongst the adult age group of people living globally. This review article documents updated pharmacological evidence and insights into the antidiabetic mechanisms of green, black, white, oolong, and pu-erh teas via reported experimental and clinical models toward encouraging their use as a complementary nutraceutical in managing the biochemical alterations found in the onset and progression of diabetes. Peer-reviewed articles published in “PubMed”, “Google Scholar”, and “ScienceDirect” from 2010 and beyond that reported the antidiabetic, antilipidemic, and digestive enzyme inhibitory effects of the selected tea types were identified. The keywords used for the literature search comprise the common or scientific names of the tea and their corresponding bioactivity. Although teas portrayed different antidiabetic pharmacological properties linked to their bioactive components, including polyphenols, polysaccharides, and amino acids, the type of phytochemical found in each tea type depends on their processing. Green tea’s strong carbohydrate digestive enzyme inhibitory effect was linked with Ellagitannins and catechins, whereas theaflavin, a main ingredient in black tea, increases insulin sensitivity via enhancing GLUT4 translocation. Theabrownin in pu-erh tea improves FBG and lipid metabolism, while chemical components in white tea attenuate prediabetes-mediated reproductive dysfunctions by improving testicular tissue antioxidant capabilities. Based on the body of findings presented in this article, it is evident that integrating tea intake into daily food consumption routines could offer a promising practical solution to support human health and well-being against diabetes disease.